Internalisasi Pemberdayaan Masyarakat dalam Meningkatkan Kualitas Permukiman Kumuh di Kota Madya Pematang Siantar - Rita Vinolia Aruan; Nelly Marina Rawaty (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
Slums are considered as parts of the town were very unproductive, dirty, do not have the potential, not efficient and unobtrusive aesthetics and beauty, where slums are often regarded as the emergence of a variety of deviant behavior, such as crime and other social ills sources. But behind it all, let us look at some areas that initially slum turned into a environmentally friendly, clean, and beautiful.Various programs have been implemented properly, people are still expectedto perform management and maintenance of the environment through pure consciousness in various forms of participation. Enterprises utilizing, foster, and preserve the natural surroundings is a positive effort in improving the quality of housing environment, because if not so then the environment will be back to slum areas.The community empowerment must still be done to maintain, improve, in order to perform maintenance of environmental quality at least equal, or, if feasible quality increases with the active participation of citizens. The success of community empowerment in the management and maintenance of settlements can be seen from the efforts undertaken, such as optimizing the function and role of institutions of formal and non-formal, define and regulate the rights, obligations and responsibilities of citizens, organize and menyelenggaranan allocation, use, supply, maintenance of land and water, and the potential of the natural environment in improving the quality of settlement environment.